FAKTOR RISIKO STATUS EPILEPTIKUS KONVULSIVUS SEBAGAI PREDIKTOR BANGKITAN STATUS EPILEPTIKUS KONVULSIVUS - Galuh Hardaningsih; Tjipta Bahtera (Media Medika Muda, 2016)
Background:Convulsive status epilepticus (CSE) is the most common childhood medical neurological emergencies, and is associated with significant morbidity and mortality. Clinico-epidemiologic characteristics and etiology of children with seizure have been emphasized as risk factors for CSE. Objective: To define the role of body temperature at onset of seizure, duration of seizure, central nervous system (CNS) infection, metabolic disorder, increased intracranial pressure, sepsis, anemia and moderate malnutrition as a predictor of CSE.Methods: The medical records of children aged between six months and 5 years with the diagnosis of CSE who were admitted to Kariadi Hospital from anuary 1st 2007 to December 31st2012 were retrospectively reviewed. In this case control study involved 80 children with CSE. Risk factors were analyzed with an odds ratio (95% confidence interval (CI)) and discriminant analysis.Results: The mean age of subjects in the case group 17.46 (SD 1.72) and in the control group 17.74 (SD 1.73) months (p > 0.05). Duration of seizure  (OR 4.74; 95%CI 2.41-9.33), temperature at onset of seizure (OR 2.5; 95%CI 1.32-4.72), CNS infection (OR 4.36; 95%CI 2.24-8.47), metabolic disorder (OR 2.18; 95%CI 1.09-4.35), increased intracranial pressure (OR 2.63; 95%CI 1.33-5.17), sepsis (OR 2.51; 95%CI 1.33-4.76), anemia (OR 3; 95%CI 1.54-5,86) and moderate malnutrition (OR 2.14; 95%CI 1.08-4.23) were risk factors for CSE in children with seizure (p<0.05). Multivariate discriminant analysis showed that the probability of had a child with those risk factors for developing into CSE was 73%.Conclusion: Duration of seizure, temperature at onset of seizure, CNS infection, metabolic disorder, increased intracranial pressure, sepsis, anemia and moderate malnutrition are risk factors for CSE which can be used as a predictor of CSE in children with seizure.Keywords: Convulsive status epilepticus, a risk factor